2019
DOI: 10.1111/apt.15299
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: suicide and IBD—a call to action

Abstract: Linked ContentThis article is linked to Malham et al papers. To view these articles, visit https://doi.org/10.1111/apt.15258 and https://doi.org/10.1111/apt.15318.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…A study of Danish and Finnish paediatric IBD patients examined cancer and mortality risks and incidentally found a fourfold increased death rate due to suicide in IBD patients compared to the general population. 10,11 Patient surveys conducted in Canada and Korea have reported more than 30% increased risk of suicide in IBD patients, similar to the findings of the present study. [27][28][29] The higher incidence rates of depression and deliberate self-harm observed in the present study in patients with IBD diagnosed over the age of 50 are consistent with a recent study from Sweden, which highlighted higher rates of suicide in individuals with late-onset IBD and Crohn's disease.…”
Section: Ta B L Esupporting
confidence: 91%
See 2 more Smart Citations
“…A study of Danish and Finnish paediatric IBD patients examined cancer and mortality risks and incidentally found a fourfold increased death rate due to suicide in IBD patients compared to the general population. 10,11 Patient surveys conducted in Canada and Korea have reported more than 30% increased risk of suicide in IBD patients, similar to the findings of the present study. [27][28][29] The higher incidence rates of depression and deliberate self-harm observed in the present study in patients with IBD diagnosed over the age of 50 are consistent with a recent study from Sweden, which highlighted higher rates of suicide in individuals with late-onset IBD and Crohn's disease.…”
Section: Ta B L Esupporting
confidence: 91%
“…7,8 Finally, IBD is associated with an increased risk of self-harm, especially among patients diagnosed with IBD in childhood. [9][10][11] A recent study in Denmark and Finland reported that deliberate self-harm was a leading cause of mortality among IBD patients. 11 However, factors associated with deliberate self-harm in patients with IBD have not been previously described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the editorial by Drs Banerjee and Gearry, the main result of the present study is the finding of an increased risk of cancer and mortality in pIBD with a surprisingly high risk of suicide. In contrast to the adult literature on this subject, the paediatric literature almost unambiguously reports an increased risk of cancer in pIBD and the main question is no longer if there's an increased risk but why.…”
supporting
confidence: 55%
“…However, to our knowledge, no studies have investigated whether differences in disease course between pUC and aUC could be explained by differences in the initial disease extent. Lastly, recent reports have found an increased risk of cancer in pIBD, possibly due to a more extensive and aggressive disease state compared to aIBD …”
Section: Introductionmentioning
confidence: 92%